Analisis Penerapan Standar Operasional Prosedur (SOP) dalam Kegiatan Perawatan Speed Boat di PT. Sinar Pacific - Nur Adindha Dewi Antasary; Jumriani Jumriani; Gradina Nur Faizah (Fakultas Teknik Universitas Cenderawasih, 2026)
This research is motivated by the importance of implementing Standard Operating Procedures (SOP) in speed boat maintenance activities as a supporting facility for ship agency operations at PT. Sinar Pasific. The high intensity of speed boat usage makes the fleet vulnerable to damage if maintenance is not carried out regularly and according to procedures. Based on initial observations, inconsistencies in maintenance implementation, incomplete documentation, and damage to the engine, electrical systems, and hull were still found, which can disrupt company operations. This study aims to determine the implementation of SOPs, the obstacles encountered, and the efforts made to optimize speed boat maintenance at PT. Sinar Pasific. This research was conducted at PT. Sinar Pasific during the author’s Onboard Practical Training (PRADA) from August 2024 to July 2025. The research method used is a descriptive qualitative method. The data sources were obtained through direct field observation, semi-structured interviews with personnel involved in speed boat operations, and documentation studies related to fleet maintenance activities. The results show that the implementation of Standard Operating Procedures (SOP) in speed boat maintenance at PT. Sinar Pasific has been carried out but has not yet run optimally. This is indicated by inconsistent maintenance schedules, lack of supervision, and incomplete maintenance documentation. In addition, several problems were still found, such as damage to the engine, electrical systems, and speed boat hulls, which can hinder company operations. To overcome these obstacles, the company has made efforts by improving discipline in SOP implementation, conducting regular supervision and evaluation, improving maintenance documentation, and increasing technicians’ understanding of the importance of preventive maintenance so that speed boat conditions are maintained and operational activities run smoothly.